Evaluation of the Efficacy and Safety of a Dual Delayed-Release Formulation of 10-mg Esomeprazole in Patients with Gastric Erosions: A Multicenter, Randomized, Double-Blind, Active-Control, Phase III Study - Hyun Lim; Ju Yup Lee; Yong Hwan Kwon; Hee Seok Moon; Jong Kyu Park; Ki Bae Kim; Sang Wook Kim; Young Hoon Youn; Sang Gyun Kim; Gwang Ha Kim; Ji Won Kim; Jae-Young Jang; et al. (Gut and Liver)
Background/Aims : Clinical data on the efficacy and safety of the dual delayed-release formulation of 10-mg esomeprazole (HIP2101) are currently limited. Therefore, this study compared the efficacy and safety of HIP2101 and 20-mg famotidine (RLD2101) in patients with gastric erosions. Methods : In this multicenter, randomized, double-blind, active-control, phase III study, 326 patients with endoscopically proven gastric mucosal erosion were randomly assigned to receive either HIP2101 or RLD2101 once daily for 2 weeks. The primary endpoint was the rate of improvement of erosion. Secondary endpoints (rate of cure of erosion and edema, and rate of improvement of hematin and gastrointestinal symptoms) and treatment-emergent adverse events were compared between the groups. Results : Based on the per-protocol set (PPS) analysis, the improvement rates for erosion were 64.9% (98/151) and 63.7% (100/157) in the HIP2101 and RLD2101 groups, respectively (95% confidence interval, –9.5 to 11.9). The lower bound of the 95% confidence interval was greater than the noninferiority margin of –14%. These results were similar to those of the full analysis set (FAS) (HIP2101 group, 64.6%; RLD2101 group, 62.7%). Based on the PPS and FAS analyses, the cure rates for erosion and edema and the improvement rates for hematin and gastrointestinal symptoms were comparable between the groups. The number of adverse events did not differ significantly between the groups. Conclusions : The efficacy and safety of HIP2101 were comparable to those of RLD2101 in the treatment of gastric erosions and symptomatic improvement. These findings suggest that HIP2101 may be a novel treatment option for gastritis (ClinicalTrials.gov identifier: NCT05024721).